Measuring Contact Pressures of phonating Vocal Fold using a Pressure-Sensing-Matrix during Hemi-Larynx Experiments - Scheible, Florian; Veltrup, Reinhard; Schaan, Casey; Lamprecht, Raphael; Staggl, Manuel; Semmler, Marion; Sutor, Alexander (Proceedings of Meetings on Acoustics, 2021)
During phonation, the vocal folds execute a complex movement. Related to the subglottal pressure and tension of the vocal folds themselves, this movement may differ, furthermore depending on the kind of phonation a collision between both vocal folds may occur. If the vocal folds are overstrained, this can cause lesions. To gain knowledge about the vocal folds movements and the way of their collisions, a high-speed evaluation unit for a pressure-mapping sensor was developed. The sensor brings along a local resolution of 27.6 measure points per square centimeter and with the developed unit an adjustable framerate up to 1 kHz can be realized. Due to a sensor thickness of about 0.2 mm, an integration into hemi-larynx flow experiments is quite simple without vigorous changes on the setup. Because of an unrestricted field of view it is possible to record the movements with a high-speed camera. These recordings will be correlated with contact pressures in the post processing. During these experiments, different flowrates of the excitation air.
CRIS-Team Scopus Importer:2024-12-16